Media Pembelajaran Gerbang Logika Pada Mata Kuliah Sistem Digital Di Universitas Katolik Musi Charitas - Jevanda BS, Klaudius; Nurmansyah, Wawan; Andiyanto, Gregorius Fredo (Majalah Ilmiah Teknologi Elektro, 2024)
This research aims to build learning media for AND, OR, NOT, NAND, NOR, XOR and XNOR logic gates for the Digital Systems course at Musi Charitas Catholic University Palembang. The Digital Systems course in the learning process is carried out theoretically and practically in accordance with the academic guidelines and curriculum of the Informatics Study Program for first semester students. In the semester learning plan (RPS) for learning outcomes that students are expected to be able to explain, understand and assemble each logic gate to match the truth table. The research stages carried out were data collection, preparing tools and materials, logic gate circuit design, logic gate circuit implementation, logic gate circuit testing and conclusions. Data collection methods used literature studies and observations at Musi Charitas Catholic University Palembang. The subjects of the research trial were 19 students of the Informatics Study Program who took digital systems courses in the odd semester of the 2023/2024 academic year. The results of the research show that the learning media for AND, OR, NOT, NAND, NOR, XOR and XNOR logic gates was produced using trials according to the truth table. The results of the descriptive trial of student responses from the aspect of suitability of the material were 73.7% strongly agree, the completeness aspect of the content was 52.6% strongly agreed, the ease of use of the media aspect was strongly agreed at 57.9%, the usability aspect of the media was 78, 9% said they strongly agree, 68.4% strongly agreed with the appearance aspect and 68.4% strongly agreed with the technical aspect. Keyword— Logic Gates; Digital System, Learning Media.